2003
DOI: 10.1523/jneurosci.23-12-05329.2003
|View full text |Cite
|
Sign up to set email alerts
|

Separation-Induced Receptor Changes in the Hippocampus and Amygdala ofOctodon degus: Influence of Maternal Vocalizations

Abstract: Relatively little is known about the basic mechanisms that play a role in the vulnerability of the developing brain toward adverse environmental influences. Our study in the South American rodent Octodon degus revealed that repeated brief separation from the parents and exposure to an unfamiliar environment induces in the hippocampal formation of male and female pups an upregulation of D1 and 5-HT1A receptor density in the stratum radiatum and stratum lacunosum moleculare of the CA1 region. In the CA3 region, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
73
0
4

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(78 citation statements)
references
References 86 publications
1
73
0
4
Order By: Relevance
“…The level of 5-HT1A-R binding in basolateral nucleus of the amygdala (BLA) is increased by maternal separation stress in rats (Vicentic et al, 2006) and Octodon degus (Ziabreva et al, 2003). Under non-stressed conditions, application of 5-HT1A-R agonists (e.g., 8-OH-DPAT) inhibits the excitability of neurons in the BLA, while the inhibitory actions of 5-HT on these neurons can be prevented by 5-HT1A-R antagonist coapplication (Cheng et al, 1998;Stein et al, 2000;Wang et al, 1999).…”
Section: Role Of 5-ht1a Receptorsmentioning
confidence: 99%
“…The level of 5-HT1A-R binding in basolateral nucleus of the amygdala (BLA) is increased by maternal separation stress in rats (Vicentic et al, 2006) and Octodon degus (Ziabreva et al, 2003). Under non-stressed conditions, application of 5-HT1A-R agonists (e.g., 8-OH-DPAT) inhibits the excitability of neurons in the BLA, while the inhibitory actions of 5-HT on these neurons can be prevented by 5-HT1A-R antagonist coapplication (Cheng et al, 1998;Stein et al, 2000;Wang et al, 1999).…”
Section: Role Of 5-ht1a Receptorsmentioning
confidence: 99%
“…The pups showed a substantial decrease in the number of nicotinamide adenine dinucleotide phosphate-diaphorase-reactive neurons in the dorsal anterior cingulate cortex and in the nucleus accumbens (Poeggel, Lange, Hase, Metzger, Gulyaeva, & Braun, 1999), and an alteration of the balance between serotonergic and dopaminergic innervation of the medial prefrontal cortex (Braun, Lange, Metzger, & Poeggel, 2000). Even short-term social separation from mothers and siblings (from P8 to P10, twice a day, each time for 3 min) resulted in an upregulation of dopaminergic and serotonergic receptor density in the hippocampus (Ziabreva, Poeggel, Schnabel, & Braun, 2003). Braun et al (2003) used neonatal degus and examined the effects of parental separation on exploratory behavior and vocalization in an open field, which was a novel environment for the pups.…”
mentioning
confidence: 99%
“…At the synaptic level such chronic deprivation alters synaptic densities and ultrastructure (7,10). Recent studies in rodents after periodic parental separation during the preweaning life span have demonstrated that, analogous to this experience-driven development of sensory and motor systems, the functional maturation of higher associative cortical regions, in particular those that are part of the limbic system, is also strongly influenced by emotional experience (11)(12)(13)(14)(15)(16)(17)(18)(19).…”
mentioning
confidence: 99%